نظام السقــي في وادي ســـوف وواد ريــــغ دراســــة مقارنــــــــــة 1854 ــ 2000 م - فاطمة معتوقي (جامعة الوادي - University of Eloued, 2025)
"تهدف هذه الدراسة إلى مقارنة نظام السقي في كل من وادي سوف وواد ريغ باعتبارهما منطقتين فلاحيتين صحراويتين تواجهان تحديات مائية متقاربة، لكنهما تختلفان من حيث أساليب استغلال المياه وإدارتها. وقد أظهرت الدراسة أن كلا المنطقتين تعتمدان بشكل رئيسي على المياه الجوفية، مع تباين في عمق الموارد وتكلفة استخراجها. كما بيّنت أن واد ريغ تتجه نحو الاعتماد على تقنيات حديثة رغم ارتفاع التكاليف، في حين تُظهر وادي سوف قدرة أكبر على التكيّف مع ندرة الموارد بفضل التنظيم المحلي وروح التعاون بين الفلاحين. وتوصي الدراسة بضرورة تعزيز التكوين، وتشجيع استعمال الطاقات المتجددة، وتحسين البنى التحتية المائية لضمان استدامة النشاط الزراعي في كلا المنطقتين. This study aims to compare the irrigation systems in Ouargla's regions of Oued Souf and Oued Righ, two desert agricultural zones facing similar water-related challenges but differing in their approaches to water exploitation and management. The research revealed that both areas rely primarily on groundwater, with notable differences in resource depth and pumping costs. Oued Righ tends to adopt modern irrigation techniques despite their high cost, while Oued Souf shows greater adaptability through local organization and cooperation among farmers. The study recommends enhancing farmer training, promoting renewable energy use, and upgrading water infrastructure to ensure sustainable agricultural development in both regions.
مذكرة ماستر قسم التاريخ تخصص المغرب العربي المعاصر
Keywords: الصحراء; الفلاحة; وادريغ; وادي سوف; نظام السقي; Irrigation system; Wadi Souf; Wadi Rig; Agriculture; Sahara